Transformasi Gang Sempit Menjadi Sentra UMKM: Model Pemberdayaan Masyarakat Go Global, Go Digital, Go Green di Kelurahan Duren Tiga - Rina Ekawati; Dadan Abdan Sakur (BADAN PENERBIT STIEPARI PRESS, 2025)
Narrow alleys in urban areas are often neglected despite their potential to be developed into productive economic spaces. This community service program aims to transform narrow alleys in Duren Tiga Village into UMKM centers implementing the concept of